Unraveling the obesity paradox in polytrauma patients: survival benefit specifically in individuals with obesity class I - Luh, Hui-Tzung; Wu, Tsung-Hung; Kuo, Lu-Ting; Chen, Shyr-Chyr; Su, Chin-Hua; Tsao, Shu-Yu; Hsieh, Sung-Tsang; Lai, Dar-Ming; Lee, Chien-Chang (Obesity (Silver Spring, Md.), 2025)
The "obesity paradox" suggests that higher BMI values might be protective in certain conditions. However, it is controversial in polytrauma patients, with different studies presenting varying results. A total of 1234 polytrauma patients were categorized by World Health Organization Asia-Pacific BMI classifications. Primary outcomes were 30- and 365-day all-cause mortality. Secondary outcome was length of hospital stay. Inverse probability of treatment weighting was performed to minimize baseline bias. Cox proportional hazards models we used to assess the impact of BMI on mortality. The 30-day mortality rates were 7.5%, 9.0%, 6.7%, 2.4%, and 2.6% for patients with underweight (<18.5 kg/m ), normal weight (18.5-22.9 kg/m ), overweight (23.0-24.9 kg/m ), obesity class I (25.0-29.9 kg/m ), and obesity class II (>30.0 kg/m ), respectively. The 365-day mortality rates were 12.5%, 15.0%, 12.6%, 7.5%, and 7.7%, respectively. Only obesity class I was associated with a significantly lower risk of 30-day (hazard ratio [HR] = 0.19, 95% CI: 0.06-0.66; p = 0.00864) and 365-day mortality (HR = 0.57, 95% CI: 0.33-0.99; p = 0.0448). Furthermore, patients with obesity class II had significantly shorter lengths of hospital stays compared with those with normal weight (mean [SE], 6.08 [7.06] vs. 12.50 [19.80] days; p < 0.001). The obesity paradox survival advantage occurs only in polytrauma patients with obesity class I, whereas these with obesity class II tend to have shorter hospital stays.